Perlindungan Data Pribadi dalam Transaksi Online Studi Putusan Nomor 235/Pdt.G/2020/Pn.Jkt.Pst (Postulat, 2023)
In Indonesia, the most recent case of personal data leakage of e-commerce consumers was the personal data leak of the Tokopedia marketplace which occurred in early May 2020. Around 91 million Tokopedia user account data were hacked and sold on the dark web for US$ 5,000. This personal data leak case a lawsuit was filed against the Minister of Communication and Informatics and PT Tokopedia and has been decided by Decision Number: 235/PDT.G/2020/PN.JKT.PST. Protection of personal data in Indonesia deserves to be studied and the problem must be resolved immediately. In this study, a normative juridical method was used and it was found that problems related to regulation also contributed to the fact that the protection of personal data of online application consumers in Indonesia was not maximized. This is due to the fact that existing laws regarding the protection of consumer personal data are still deemed unable to overcome the problems. In addition to regulatory issues, there are also problems regarding the government's lack of oversight of online applications that surf in cyberspace that collect personal data of application users. In this case, it is necessary to immediately pass the Bill on Personal Data Protection.